Targeting the Complement Pathway in Malignant Glioma Microenvironments - Zhu, Hongtao; Yu, Xingjiang; Zhang, Suojun; Shu, Kai (Frontiers in Cell and Developmental Biology, 2021)
Malignant glioma is a highly fatal type of brain tumor, and its reoccurrence is largely due to the highly ordered interactions among its various microenvironmental components. Besides its role in the regulation of immune surveillance and clearance under physiological conditions, the complement system is also expressed in a variety of tumor types and is widely involved in the interactions with the tumor microenvironments. Recent studies have shown that complement signaling molecules are widely expressed in the tumor microenvironment and various tumor cells, including malignant glioma cells. And the complement system participates in tumor growth, immunosuppression, and phenotype transition. In this review, we enumerate the expression and function of complement molecules in a variety of tumors that have been reported. Moreover, we elaborate on the role of the complement pathway in glioma cells and various components of malignant glioma microenvironments. Finally, we summarize the possibility of the complement molecules as prognostic factors and therapeutic targets in the treatment of malignant glioma. We believe that targeting the complement pathway will play a significant role in the future treatment of multi-type tumors, including malignant glioma.